2011
DOI: 10.1111/j.1447-0756.2010.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of atypical polypoid adenomyoma that possibly underwent a serial progression from endometrial hyperplasia to carcinoma

Abstract: Atypical polypoid adenomyoma is a rare uterine tumor composed of atypical endometrial glands, which often exhibit squamous metaplasia, and a cellular smooth muscle stroma. Although atypical polypoid adenomyoma is categorized as a benign lesion, it is reportedly associated with endometrial cancer, and it shows persistence and recurrence even after conservative medical treatment. We present a rare case of atypical polypoid adenomyoma that possibly underwent a serial pathological change from endometrial hyperplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…Our study involves the longest follow-up period in conjunction with treatment of APA. The prognosis of APA is thought to be good (even though some patients with local excision of tumors progress to endometrial cancer or coexisting endometrial cancer after several years of followup) [3,6,15], and our data also show a good prognosis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Our study involves the longest follow-up period in conjunction with treatment of APA. The prognosis of APA is thought to be good (even though some patients with local excision of tumors progress to endometrial cancer or coexisting endometrial cancer after several years of followup) [3,6,15], and our data also show a good prognosis.…”
Section: Discussionsupporting
confidence: 53%
“…It is a polypoid tumor of the uterus composed of endometrial gland cells admixed with a stromal component of interlacing bundles of smooth muscle [1]. Although APA was previously considered to be a benign tumor, recent studies demonstrated its malignant potential and a high recurrence rate, leading to malignant transformation [2][3][4][5][6]. Hence, hysterectomy is the primary therapeutic choice for patients with APA.…”
Section: Introductionmentioning
confidence: 99%
“…APA is basically classified as a benign disease; however, APA with marked complex glandular structures has been proposed as ‘APA with low malignant potential’ (APA‐LMP) to emphasize the potential risk for myometrial invasion and the possibility of recurrence or persistence after local excision . Moreover, APA can co‐exist with endometrial carcinoma and may even undergo carcinomatous transformation . The risk for endometrial carcinoma is estimated to be around 10% in patients with APA, much higher than that in healthy women.…”
Section: Introductionmentioning
confidence: 99%
“…It has an architecturally complex and cytologically atypical glandular component that can be confused with well-differentiated adenocarcinoma. Although APA was previously considered a benign tumor, recent studies have demonstrated its malignant potential and high recurrence rate, leading to malignant transformation (1)(2)(3)(4)(5)(6)(7). Because it typically occurs in premenopausal women (1) and mainly in women of reproductive age (2), we come across patients who want to preserve their reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%